Ammonia gas detection using field-effect transistor based on a solution-processable organic semiconductor. (December 2018) - Rajeev, V.R.; Paulose, Akhil K.; Unni, K.N. Narayanan
Abstract: We have developed a regioregular poly (3-hexylthiophene) (rr-P3HT) based organic field-effect transistor (OFET) for the detection of low concentration of ammonia (NH3 ) gas. The ammonia sensing mechanism of OFET based sensor device can be described in terms of the chemical interaction between NH3 and P3HT. Upon exposing the conducting channel to various concentrations of ammonia, a reduction in source-drain current/mobility, and an increase in threshold voltage were observed. This deterioration of the performance parameters of the OFET while exposing to different concentrations of ammonia was attributed to the dedoping effect. Our OFET based ammonia sensor could detect ammonia gas concentrations in the range 20 ppm–100 ppm. Moreover, the device showed excellent recovery to the initial state within a few minutes. Highlights: Developed a regioregular poly(3-hexylthiophene)organic field-effect transistor by solution processing for ammonia sensing. Fabricated OFET sensor could be used for sensing ammonia concentration in the range between 20 ppm and 100 ppm. The sensing mechanism of the sensor device could be attributed to dedoping effect. The sensor got restored to almost 90% of its original state within 6 min after the removal of ammonia.